Complexation‐Induced Supramolecular Assembly Drives Metal‐Ion Extraction. Issue 40 (28th August 2014) - Ellis, Ross J.; Meridiano, Yannick; Muller, Julie; Berthon, Laurence; Guilbaud, Philippe; Zorz, Nicole; Antonio, Mark R.; Demars, Thomas; Zemb, Thomas
Abstract Combining experiment with theory reveals the role of self‐assembly and complexation in metal‐ion transfer through the water–oil interface. The coordinating metal salt Eu(NO3)3 was extracted from water into oil by a lipophilic neutral amphiphile. Molecular dynamics simulations were coupled to experimental spectroscopic and X‐ray scattering techniques to investigate how local coordination interactions between the metal ion and ligands in the organic phase combine with long‐range interactions to produce spontaneous changes in the solvent microstructure. Extraction of the Eu3+–3(NO3−) ion pairs involves incorporation of the "hard" metal complex into the core of "soft" aggregates. This seeds the formation of reverse micelles that draw the water and "free" amphiphile into nanoscale hydrophilic domains. The reverse micelles interact through attractive van der Waals interactions and coalesce into rod‐shaped polynuclear EuIII‐containing aggregates with metal centers bridged by nitrate. These preorganized hydrophilic domains, containing high densities of O‐donor ligands and anions, provide improved EuIII solvation environments that help drive interfacial transfer, as is reflected by the increasing EuIII partitioning ratios (oil/aqueous) despite the organic phase approaching saturation. For the first time, this multiscale approach links metal‐ion coordination with nanoscale structure to reveal the free‐energy balance that drives the phase transfer of neutral metal salts.